Analisis Tingkat Penerimaan Dan Penggunaan Aplikasi Evaluasi PBM Menggunakan Model UTAUT (Unified Theory of Acceptance and Use of Technology) yang Diperluas Di Universitas Negeri Padang - Suci Indah Kemala Dewi; Denny Kurniadi; Titi Sriwahyuni (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2018)
Padang state university is one of the universities that provide the academicians with information system in order to make them easier when looking for information that they need. One of the information systems is online learning evaluation system. The aim of this research is examining some factors that impacting the acceptance and the usage of online learning evaluation system interest by using Venkatesh's model (2003) that is Unified Theory of Acceptance and Use of Technology (UTAUT). Variables that used are: performance expectancy, effort expectancy, social influence, facilitating condition and hedonic motivation. The result of the data analysis shows that the variables of performance expectancy, effort expectancy, social influence, facilitating conditions and hedonic motivation together have a significant effect of 67% on the interest of acceptance and use of Online Learning Evaluation Information System at State University of Padang. So it can be concluded that the factors of performance expectancy, effort expectancy, social influence, facilitating conditions and hedonic motivation have contributed to the interest of acceptance and use of the system. If each variable has a higher correlation it will increase the acceptance of Information Systems Online Learning Evaluation at State University of Padang.Keywords: Unified Theory Of Acceptance And Use Of Technology (UTAUT), performance Expectancy, Effort Ecpectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Online Learning Evaluation